2020
DOI: 10.1016/j.gca.2020.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium complexation and hydration in chloride-rich hydrothermal fluids: A combined ab initio molecular dynamics and in situ X-ray absorption spectroscopy study

Abstract: Accurate knowledge of rare earth elements (REE) speciation in high pressurehigh temperature fluids is required to model REE transport and precipitation in subduction zones and magmatic-hydrothermal environments, and the formation of rare metal deposits. Recent experiments (lanthanum, ytterbium, erbium) have demonstrated that REE chloride complexes are the main REE form in many hydrothermal fluids (Migdisov, et al., 2016). However, the speciation of yttrium *Manuscript (Y(III)), a cation with an ionic radius si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 90 publications
(86 reference statements)
2
9
0
Order By: Relevance
“…However, temperature affects LREE and HREE differently (Fig. 2): Gd and Yb display a retrograde solubility from 100 °C onwards, similar to what we previously reported for Eu, Yb, or Y in acidic Cl-and S-bearing solutions 26,27,44 ; on the contrary, La solubility increases suddenly from below detection limit (~10 ppm) at T < 300 °C (e.g., absorption edge is barely visible on Fig. 1A) to more than 10 times the detection limit at 400-500 °C (Figs.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…However, temperature affects LREE and HREE differently (Fig. 2): Gd and Yb display a retrograde solubility from 100 °C onwards, similar to what we previously reported for Eu, Yb, or Y in acidic Cl-and S-bearing solutions 26,27,44 ; on the contrary, La solubility increases suddenly from below detection limit (~10 ppm) at T < 300 °C (e.g., absorption edge is barely visible on Fig. 1A) to more than 10 times the detection limit at 400-500 °C (Figs.…”
Section: Resultssupporting
confidence: 85%
“…1A and 2A). This is the first time we observe prograde solubility for an REE in our in situ experiments 26,27,44 .…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The BLYP functional generally provides a good description of the structural properties of water including O-O interactions, H-bond statistics, angular distributions, coordination numbers, and radial distribution functions when compared with experiments (Gillan et al, 2016;Lin et al, 2012). However, as discussed in our previous studies using the BLYP exchange correlation functional (Mei et al, 2018;Guan et al, 2020), we note that there is a well-known tendency for most functionals, including BLYP, to overstructure liquid water (Lee and Tuckerman, 2006;Lin et al, 2012). For example, Bankura et al (2014) showed that BLYP, like most other functionals, best reproduces the hydrogenbonded network of water at ambient conditions when using an elevated temperature (80 °C in their case), and it could be argued that there is a temperature offset of approximately 50-55 °C between the computed data as compared to the experimental structure of the solvent at room temperature.…”
Section: Ab Initio Molecular Dynamics Simulationsmentioning
confidence: 96%
“…Ab initio molecular dynamic simulations (MD) are an effective method to predict metal complexes and their thermodynamic properties [1] and offer the opportunity to achieve conditions that cannot be reached via the experimental approach. Our group has obtained new properties for the Y(III)-Cl - [2], Y(III)-SO 4 2and La(III)-Clcomplexes at temperature up to 500 ˚C, 600 to 1000 bar via MD studies. The predicted geometries are supported by in-situ XAS measurements conducted over similar P-T-X range.…”
mentioning
confidence: 99%